2020
DOI: 10.1093/jbcr/iraa085
|View full text |Cite
|
Sign up to set email alerts
|

Evaluate the Effect of Zinc Oxide and Silver Nanoparticles on Biofilm and icaA Gene Expression in Methicillin-Resistant Staphylococcus aureus Isolated From Burn Wound Infection

Abstract: Methicillin-resistant Staphylococcus aureus is the cause of nosocomial and community-acquired infections. This study aimed to evaluate the effect of zinc oxide and silver nanoparticles (ZnO-Ag NPs) on biofilms formation and icaA gene expression in methicillin-resistant S. aureus (MRSA). In this study, three standard strains (ATCC 43300, 25923, and 29913) and a clinical isolate are included. The minimum inhibitory concentration (MIC) of nanoparticles was determined by microdilution broth method. The antibacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…In comparison, CurBF2-AgNPs showed antibacterial activity against only S. aureus with inhibition zone of 7.33 ± 0.29 mm (Table 2). These results demonstrate that the combination of ZnO NPs with CurBF2-AgNPs gives a synergistic antibacterial effect [25] as compared to AgNPs or ZnO NPs alone.…”
Section: Inhibition Zone Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…In comparison, CurBF2-AgNPs showed antibacterial activity against only S. aureus with inhibition zone of 7.33 ± 0.29 mm (Table 2). These results demonstrate that the combination of ZnO NPs with CurBF2-AgNPs gives a synergistic antibacterial effect [25] as compared to AgNPs or ZnO NPs alone.…”
Section: Inhibition Zone Methodsmentioning
confidence: 66%
“…Dhara, S. et al investigated the decoration of AgNPs on ZnO nanoflowers impregnated on eggshell membranes and Eshraghi et al reported the effect of the incorporation of ZnO and AgNPs on bacterial biofilms. These studies showed that AgNPs decorated on ZnO enhanced the latter's antimicrobial activity [24,25].…”
Section: Introductionmentioning
confidence: 97%
“…However, Gheidar et al reported that the expression of icaA and icaD genes in the presence of ZnO-NPs were not significantly reduced compared to the control samples. But, exposure to nanoparticles reduced the expression of fnbA and fnbB genes from 0.46 to 0.06 [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only a recent study carried out in Iran documented that the sub-minimum inhibitory concentration of ZnO-Ag NPs significantly reduced the ica A gene expression in S. aureus strains [ 39 ]. Another study conducted in Korea evaluated the inhibitory effect of ZnO NPs on Pesudomonase aeruginosa biofilms genotypically [ 40 ], where the transcriptional and mutant data indicated that ZnO NPs inhibited Pesudomonase aeruginosa biofilm formation via the czcRS two-component system, which controls the QS-controlled phenotypes such as biofilm formation. This confirms the efficacy of ZnO NPs as an antibiofilm substance among a broad range of Gram positive and Gram negative bacterial isolates.…”
Section: Discussionmentioning
confidence: 99%